Integration of mobile control systems into intermodal container transportation management - Andziulis, Arūnas; Jakovlev, Sergej; Adomaitis, Danielius; Dzemydienė, Dalė (Transport, 2012)
Over the last few years, a large number of researches have emerged and approached the use of mobile expert systems and other information management technologies in the area of intermodal container transportation and decision support. However, practitioner literature poorly analyzes the process of monitoring cargo transportation conditions, cargo information security and other important issues. The paper presents an emerging field of intermodal container transportation where the primary objective of the proposed mobile control system is to monitor cargo conditions during transportation in a real time manner and work as a decision support system. Also, the article evaluates potential risks involved in cargo transportation and therefore provides mobile cargo security assurance service. Computational results suggest using an optimum number of RFID and sensor readings to effectively manage the newly proposed elements of operation strategy in a conceptual strategy framework. The overall results indicate that the integration of risk management practice into transportation processes via a mobile control system increases intermodal container transportation mobility, safety and overall effectiveness.First Published Online: 30 Mar 2012